2018
DOI: 10.1177/2325967118756576
|View full text |Cite
|
Sign up to set email alerts
|

Existing Evidence on Ultrasound-Guided Injections in Sports Medicine

Abstract: Office-based ultrasonography has become increasingly available in many settings, and its use to guide joint and soft tissue injections has increased. Numerous studies have been conducted to evaluate the use of ultrasound-guided injections over traditional landmark-guided injections, with a rapid growth in the literature over the past few years. A comprehensive review of the literature was conducted to demonstrate increased accuracy of ultrasound-guided injections regardless of anatomic location. In the upper e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(52 citation statements)
references
References 55 publications
0
47
0
2
Order By: Relevance
“…The results of this study were put into practice by Dankarini et al, showing significant clinical improvement of foot pain following US-guided injections for up to 3 months in the majority of those treated [70]. As the use of ultrasound in clinical practice continues to rise, US-guided injections could prove to be a safe way to manage foot and ankle OA pain non-surgically, however more data is needed to assess its efficacy and cost-effectiveness [71].…”
Section: Injection Techniquementioning
confidence: 76%
“…The results of this study were put into practice by Dankarini et al, showing significant clinical improvement of foot pain following US-guided injections for up to 3 months in the majority of those treated [70]. As the use of ultrasound in clinical practice continues to rise, US-guided injections could prove to be a safe way to manage foot and ankle OA pain non-surgically, however more data is needed to assess its efficacy and cost-effectiveness [71].…”
Section: Injection Techniquementioning
confidence: 76%
“…Our hypothesis that ultrasound-guided interventions demonstrate greater precision than blind infiltrations has been validated. Enough evidence can be found in the literature to support the need to use ultrasound in shoulder infiltrations (4,17- 19). In contrast, a recent Cochrane review concluded that the cost of ultrasound does not justify its use (20).…”
Section: Discussionmentioning
confidence: 99%
“…To date, it must be kept in mind that the clinical results of an invasive technique that is not performed in an ultrasound-guided manner cannot be analyzed. Multiple studies show that, without ultrasound control, a very significant number of infiltrations end up outside the "target" site (8,17,19). Therefore, the clinical results do not correlate with said procedure20.…”
Section: Discussionmentioning
confidence: 99%
“…3,16 Accuracy rates of US-guided procedures in the hip were reported between 97% and 100% with a few cases of incorrect needle positioning. 17 As in other joints, there is no standard approach to USguided intra-articular injections in the hip. The purpose is to place the needle tip in the joint space avoiding sensitive structures.…”
Section: Hip Intra-articular Injection/aspirationmentioning
confidence: 99%